School of Education : center of excellence project. (Manila, Philippines : Centro Escolar University Research and Development Center, 2013)
This module on CB-PAST does not stand alone. It is an interconnected system within a bigger system education that needs to be neatly woven to get good results.
Assessment Learning 1 -- Assessment Learning 2 -- Child and Adolescent Development -- Curriculum Development -- Developmental Reading 1 -- Developmental Reading 2 -- Educational Technology 1 -- Educational Technology 2 -- Facilitating Learning -- Practice Teaching -- Principles of Teaching 1 -- Principles of Teaching 2 -- Social Dimensions in Education -- Special Topics in Education -- The teaching profession.
CEU-COE NCBTS-based in-service teacher training modules.
Includes bibliographical references.
Keywords: EDUCATION -- PHILIPPINES